Revisiting depot medroxyprogesterone - Mehta, Sumita; Kale, Ekta; Rashid, Fatima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Injectable contraceptives form an important part of method mix of effective contraceptives used by women worldwide. Depot medroxyprogesterone (DMPA) is a long acting contraceptive which is safe, reversible and does not require any user action to maintain its efficacy. Methods: This was a prospective questionnaire based study conducted on 84 women who were acceptors of DMPA. The women were interviewed by the same health worker in the local language using a preset questionnaire which included questions regarding the demographic profile, contraceptive choices and positive and negative experiences related to usage of Injection DMPA. Results: Majority of the women were multiparous, between 25-30 years and were housewives. 19% women had started depo-provera after having one child while 87% started DMPA after their second child. The most common source of information about the contraceptive method was health care worker in 51.1% followed by friends in 30.9% and media in 17.8%. 53 women in the study group chose injection DMPA as it was convenient and safe. The most common side effect seen was amenorrhea followed by irregular bleeding, weight gain and pain abdomen. 91.6% women were satisfied with it and would recommend it to other women. Conclusions: Addressing the unmet need of family planning requires not only recruiting new clients but also assuring that women continue to use the contraceptive. Method related myths and concerns are an important reason for high discontinuation rates which need to be addressed during counselling sessions.